Gamifikasi Dalam Pembelajaran Jarak Jauh Untuk Meningkatkan Interaksi Sosial Mahasiswa: Studi kualitatif - Emy Junaidah; Damimah Damimah (Edu Berkah Khatulistiwa, 2026)
This study aims to analyze the role of gamification in distance learning as a strategy to enhance students’ social interaction. This research employed a qualitative descriptive approach, with data collected through in-depth interviews, participatory observation, and documentation. The participants consisted of two lecturers and five students from the Biology Education Study Program at Universitas Negeri Malang. Data were analyzed using thematic analysis. The findings indicate that prior to the implementation of gamification, students’ social interaction was relatively low. After integrating gamification elements such as points, interactive quizzes, leaderboards, and group challenges, there was a significant increase in participation, collaboration, and communication. This study contributes to the limited body of research on gamification in Indonesian distance learning contexts, particularly in relation to social interaction. However, challenges such as excessive focus on points and technical constraints were also identified.